ANALISIS KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG SAHAMNYA TERGOLONG BLUE CHIP YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2007 2010 - B31110120, Herson Na'U (Jurnal Manajemen Update, 2013)
ABSTRACT The authors are research on the banking financial sector companies whose share belong to the blue chip stocks listed on the Indonesia Stock Exchange with criteria based blue chip LQ45 Index covering the period 2007-2010 PT Bank Rakyat Indonesia Tbk, PT Bank Mandiri Tbk, PT Bank Central Asia Tbk, and PT Bank Danamon Indonesia Tbk. This study aims to determine how the financial performance and to determine the difference in financial performance between the Government and the Banks Private Bank. Method which used in this research is to use method of CAMEL (Capital, Assets, Management, Earnings, and Liquidity) and Test of t Free Sample (Independent T-Test). Test Free Sample t (Independent T-Test) this used to know comparison flatten to flatten two case groups. From result of analysis use method of CAMEL known that financial performance of company of banking which its share included in share of blue chip of year 2007 up to year 2010 healthy in a condition. just Only in the year monetary 2008 performance of PT Bank Central Asian Tbk enter in indisposed criterion, this matter is caused at that moment happened global crisis which cause Bank of BCA interesting of invested fund. Result of examination of hypothesis by using Test of t Free Sample (Independent T-Test), please conclude that no difference of monetary performance which expressed in value of CAMEL between the Government Bank and the Private Bank. Therefore difference of mean of CAMEL descriptively with difference of mean (difference mean) existing have the character of not significant. Its conclusion that monetary performance both bank faction that is between the Government Bank and the Private Bank is same. Key Words : Blue Chip and Ratio of CAMEL